2021
DOI: 10.1038/s41598-021-84688-7
|View full text |Cite
|
Sign up to set email alerts
|

The duration-energy-size enigma for acoustic emission

Abstract: Acoustic emission (AE) measurements of avalanches in different systems, such as domain movements in ferroics or the collapse of voids in porous materials, cannot be compared with model predictions without a detailed analysis of the AE process. In particular, most AE experiments scale the avalanche energy E, maximum amplitude Amax and duration D as E ~ Amaxx and Amax ~ Dχ with x = 2 and a poorly defined power law distribution for the duration. In contrast, simple mean field theory (MFT) predicts that x = 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 63 publications
4
44
0
Order By: Relevance
“…8). All other avalanche parameters have been evaluated by Salje et al (2019) and were confirmed by optical microscopy by Casals et al (2021a).…”
Section: Moving Twin Boundariesmentioning
confidence: 90%
See 4 more Smart Citations
“…8). All other avalanche parameters have been evaluated by Salje et al (2019) and were confirmed by optical microscopy by Casals et al (2021a).…”
Section: Moving Twin Boundariesmentioning
confidence: 90%
“…This is not true for long and smooth A(t) functions. Various scalings E ~ A X with 2 < x < 3 are discussed in literature (Casals et al 2019(Casals et al , 2020(Casals et al , 2021aMcFaul et al 2020).…”
Section: Energy Ementioning
confidence: 99%
See 3 more Smart Citations